2020
DOI: 10.1177/0194599820932128
|View full text |Cite
|
Sign up to set email alerts
|

Predicting COVID‐19 Incidence Using Anosmia and Other COVID‐19 Symptomatology: Preliminary Analysis Using Google and Twitter

Abstract: Objective To determine the relative correlations of Twitter and Google Search user trends concerning smell loss with daily coronavirus disease 2019 (COVID-19) incidence in the United States, compared to other severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) symptoms. To describe the effect of mass media communications on Twitter and Google Search user trends. Study Design Retrospective observational study. Setting United States. Subjects and Methods Google Search and “tweet” frequency concerning CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 7 publications
1
53
0
2
Order By: Relevance
“…Others have also seen significant discrepancies between self‐report and psychophysical olfactory test measures 21‐23 . Interestingly, the prevalence rate observed in self‐report studies appears to be positively correlated with the amount of attention in the popular press paid to COVID‐19's impact on the ability to smell 24 …”
Section: Discussionmentioning
confidence: 99%
“…Others have also seen significant discrepancies between self‐report and psychophysical olfactory test measures 21‐23 . Interestingly, the prevalence rate observed in self‐report studies appears to be positively correlated with the amount of attention in the popular press paid to COVID‐19's impact on the ability to smell 24 …”
Section: Discussionmentioning
confidence: 99%
“…The users on this social media are also interested in informing and warning their friends and followers about COVID-19 (Abd-Alrazaq et al, 2020). The spread of COVID-19 in any geographical area has led to the growth of the number of tweets and hashtags related to this disease (Bisanzio et al, 2020;Golder et al, 2020;Klein et al, 2020) and also an increase in the search for information about the symptoms of this disease (Panuganti et al, 2020). An analysis of tweets shared by users in the United States indicated that people seek information about government measures on Corona, the number of people infected in the country and the world, and prevention and treatment methods against COVID-19 (Yum, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Twitter has announced 330 million active monthly users in its firstquarter statistics for 2019 (Kullar et al, 2020). As a social media platform, Twitter facilitates user-generated thoughts, feelings, and health condition real-time research with concomitant demographic information (Panuganti et al, 2020). Top tweets included 'likes', 'retweets', and 'comments.…”
mentioning
confidence: 99%
“…The aim of this survey was to anonymously collect details from patients complaining of SOL with regards to the assumed correlation with COVID-19 infection, similarly to studies performed in other countries [19].…”
Section: Methodsmentioning
confidence: 99%
“…In January 2020, the Chinese authorities shared the full sequence of the novel coronavirus genome and made the data available to researchers worldwide. This novel coronavirus was later designated as Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) and the disease named as Coronavirus disease 2019 (COVID- 19) in February 2020 by the World Health Organization (WHO) [3,4]. Thus far, SARS-CoV-2 had spread worldwide and the WHO, on March 11, declared COVID-19 a pandemic with the sustained risk of further global spread [5][6][7].…”
Section: Introductionmentioning
confidence: 99%